Does It Look Good or Evil? Children’s Recognition of Moral Identities in Illustrations of Characters in Stories - Obiols-Suari, Núria; Marco-Pallarés, Josep (Frontiers in Psychology, 2021)
Children usually use the external and physical features of characters in movies or stories as a means of categorizing them quickly as being either good or bad/evil. This categorization is probably done by means of heuristics and previous experience. However, the study of this fast processing is difficult in children. In this paper, we propose a new experimental paradigm to determine how these decisions are made. We used illustrations of characters in folk tales, whose visual representations contained features that were compatible or incompatible with the moral identity of the characters. Sixteen children between 8 and 10 years old participated in the experiment. We measured their electrodermal activity when they were listening to the story and looking at pictures of the characters. Results revealed a higher increase in skin conductance when the illustrations showed a moral condition that was incompatible with the actions of a character than when they showed one that was compatible. These results suggest that children make fast decisions about the moral identity of characters based on their physical features. They open up new possibilities in the study of the processing of moral decisions in children.